2018
DOI: 10.1080/01596306.2018.1457626
|View full text |Cite
|
Sign up to set email alerts
|

‘It is like school sometimes’: friendship and sociality on university campuses and patterns of social inequality

Abstract: Whilst most social and educational research on friendship focuses on children at school, it remains a crucially important factor for students in higher educationand can play a key role in the maintenance, exacerbation or subversion of dominant forms of social inequalities. This paper explores the complexities of such dynamics in relation to friendship and social life at university, utilizing data from an in-depth qualitative study of HE students at a UK campus university. Students stressed the importance of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Our qualitative data suggested that timing of social events around commutes, as well as start times of lectures and availability of suitable space on campus, were all important to students. This is in broad agreement with what others have found (Thomas & Jones, 2017), and is not unique to this institution; the difficulties for traditionally atypical students have been recognised in the literature (Read et al, 2018;Pokorny et al, 2017;Carruthers Thomas, 2016;Rubin & Wright, 2015;Read et al, 2003).…”
Section: 'Being a Commuting Student Not Around As Much'supporting
confidence: 91%
See 1 more Smart Citation
“…Our qualitative data suggested that timing of social events around commutes, as well as start times of lectures and availability of suitable space on campus, were all important to students. This is in broad agreement with what others have found (Thomas & Jones, 2017), and is not unique to this institution; the difficulties for traditionally atypical students have been recognised in the literature (Read et al, 2018;Pokorny et al, 2017;Carruthers Thomas, 2016;Rubin & Wright, 2015;Read et al, 2003).…”
Section: 'Being a Commuting Student Not Around As Much'supporting
confidence: 91%
“…Aspects such as living arrangements and commuting status affect access (Read et al, 2018;Thomas & Jones, 2017); additionally social activities often organised by clubs and societies may exclude some student groups for cultural, personal or religious reasons if they include alcohol, inadvertently making them feel that they do not belong (Jacobs et al, 2018). This is of relevance in a proudly multi-cultural institution such as this.…”
Section: 'Being a Commuting Student Not Around As Much'mentioning
confidence: 99%
“…It is clear that the development of social relationships with students and staff, is an intrinsic part of belonging, for both groups. Interpersonal relationships including those with peers are important determinants of belonging in students (Katanis, 2000;Johnson, 2012;Read et al, 2018;Meehan & Howells, 2019), and the potential negative impact of the pandemic on relationships has also been highlighted by others (Longhurst et al, 2020). Developing relationships is easier on campus where informal and spontaneous face-to-face contacts with others are possible (Tinto, 1993;Simpson, 2003;Strayhorn, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is known to positively impact upon student engagement and attainment (Hausman et al, 2009;Freeman et al, 2007), so enhancing feelings of belonging is important for educational institutions as well as individuals. The physical space of the campus affords students opportunities to meet each other and to develop and strengthen social relationships with each other and academic staff (Samura, 2018), which is intrinsic to developing a sense of belonging and a secure learner identity (Kahu & Nelson, 2018;Read et al, 2018).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Prior studies have demonstrated that undergraduates from under-represented backgrounds can find it difficult to fit in and experience a sense of belonging in university settings (Bathmaker et al, 2016;Finnegen & Merrill, 2017;Perez-Adamson & Mercer, 2016;Read, Burke, & Crozier, 2018;Reay, Crozier, & Clayton, 2009;Reay et al, 2010).…”
Section: Social and Academic Experiences Of Elite Universitiesmentioning
confidence: 99%